Formation and control of bromate in sulfate radical-based oxidation processes for the treatment of waters containing bromide: A critical review. (1st June 2020) - Guan, Chaoting; Jiang, Jin; Pang, Suyan; Zhou, Yang; Gao, Yuan; Li, Juan; Wang, Zhen
Abstract: Sulfate radical-based advanced oxidation processes (SR-AOPs) show a good prospect for effective elimination of organic contaminants in water due to the powerful oxidation capability and good adaptability of sulfate radical (SO4 − ). However, great concerns have been raised on occurrence of the carcinogenic byproduct bromate (BrO3 − ) in SR-AOPs. The present article aims to provide a critical review on BrO3 − formation during bromine (Br)-containing water oxidation by various SR-AOPs. Potential reaction mechanisms are elaborated, mainly involving the sequential oxidation of bromide (Br − ) by SO4 − to Br-containing radicals (e.g., bromine atom (Br)) and then to hypobromous acid/hypobromite (HOBr/OBr − ), which acts as the requisite intermediate for BrO3 − formation. Some key influencing factors on BrO3 − formation are discussed. Particularly, dissolved organic matter (DOM) as a component ubiquitously present in aquatic environments shows a significant suppression effect on BrO3 − formation, primarily attributed to the reduction of Br by DOM to Br − . The reaction of Br with DOM can hardly produce organic brominated byproducts, while their formation is mainly due to the bromination of HOBr/OBr − generated through nonradical pathways such as the direct reaction of Br − with oxidants (e.g., peroxymonosulfate (PMS)) or other reactive species derived from catalytic activators (e.g., Co(III) in the Co(II)/PMS process). The debromination of brominated pollutants during their oxidation by SO4 − results in the release of Br −, which, however, is not further transformed to BrO3 − until coexisting organic matters are mineralized nearly completely. Furthermore, possible strategies for control of BrO3 − formation in SR-AOPs as well as the future research needs are proposed. Graphical abstract: Image 10091 Highlights: BrO3 − formation mechanisms during oxidation of Br − by SR-AOPs are elaborated. Suppression effect of DOM on BrO3 − formation by SR-AOPs is discussed. BrO3 − formation from oxidation of brominated pollutants is explicated. Possible strategies for controlling BrO3 − formation in SR-AOPs are proposed.